2020
DOI: 10.4102/sajhivmed.v21i1.1105
|View full text |Cite
|
Sign up to set email alerts
|

Patient acceptance of HIV testing services in rural emergency departments in South Africa

Abstract: Background South Africa faces the highest burden of HIV infection globally. The National Strategic Plan on HIV recommends provider-initiated HIV counselling and testing (HCT) in all healthcare facilities. However, HIV continues to overwhelm the healthcare system. Emergency department (ED)-based HCT could address unmet testing needs. Objectives This study examines the reasons for accepting or declining HCT in South African EDs to inform the development of HCT implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Patient acceptance of ED-based HCT, in South Africa and elsewhere, is encouragingly high [ 1 , 4 6 , 24 , 33 , 34 ]. Our study revealed that 92% of patients expressed support for ED-based HCT, and 80% were willing to undergo testing, if available–findings which are consistent with other contexts [ 3 , 5 , 24 , 33 , 35 ]. Despite this reassuringly high acceptance combined with innovative measures undertaken by the government to reach all vulnerable, high-risk populations with HCT, an estimated 10% of HIV positive South Africans remain unaware of their status and 15% of all new infections globally continue to occur here [ 10 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Patient acceptance of ED-based HCT, in South Africa and elsewhere, is encouragingly high [ 1 , 4 6 , 24 , 33 , 34 ]. Our study revealed that 92% of patients expressed support for ED-based HCT, and 80% were willing to undergo testing, if available–findings which are consistent with other contexts [ 3 , 5 , 24 , 33 , 35 ]. Despite this reassuringly high acceptance combined with innovative measures undertaken by the government to reach all vulnerable, high-risk populations with HCT, an estimated 10% of HIV positive South Africans remain unaware of their status and 15% of all new infections globally continue to occur here [ 10 ].…”
Section: Discussionsupporting
confidence: 87%
“…Emergency Departments (ED) are a potential venue to expand access to HIV counselling and testing (HCT) services to otherwise missed populations [1][2][3]. In the United States, ED-based HCT has had a significant impact on improving the rates of HIV diagnosis and subsequent linkage to care [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight studies reported on this step [20,23,24,[26][27][28]31,[33][34][35][37][38][39]41,44,45,[47][48][49][50][51][52][53][54][55][56][57][58]: 15 cohort studies, 10 crosssectional and three of mixed design. Twenty-four studies (86%) provided a clear definition of the step (Table 2).…”
Section: Linkage To Pre-art Carementioning
confidence: 99%
“…A total of 52 studies reported numbers or percentages of patients retained at this step [8,[20][21][22][23][24][25][26][27][28][29][30][31][32]34,36,[40][41][42][43]46,56,58,65,68,69,[72][73][74][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][95][96][97][98][99]. The majority of studies (32 studies, 62%) covering this step were longitudinal studies.…”
Section: Viral Suppressionmentioning
confidence: 99%